Technology Integration in the EFL Classrooms of Rural Bangladesh: A Wind of Change - Md. Akramuzzaman (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The study is to find out the potential opportunity to offer and possible challenges to face in implementing technology in the EFL classrooms in low-tech community such as rural Bangladesh. The data was collected from seven EFL teachers of rural middle schools of rural Bangladesh through semi-structured interviews. A purposive sampling was done to select the interviewees. The semi-structured interview information was explained for an interpretive qualitative study which used thematic analysis technique to identify the opportunities and challenges that technology can offer in the development of EFL teaching and learning in rural Bangladesh. The study is significant because technology integration comes with the promises of a better learning opportunity in a low-tech, low-resourced community, and problems to use right kind of technology in right way. Teachers’ opinions in this regard are instrumental because they the frontliners in the way of bringing a change in EFL learning through technology integration. Knowing the challenges and their proposed solutions from the perspectives of the teachers is the other side of the coin equally important to be considered.   The Study finds that technology integration in EFL learning bears the potential to offer a better teaching learning environment despite some of the challenges in rural EFL classrooms in Bangladesh.